2019
DOI: 10.1016/j.bcab.2019.101152
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of water extract of Cinnamomum burmannii bark to ascertain its in vitro antidiabetic and antioxidant activities

Abstract: NOTICE: this is the authors' version of a work that was accepted for publication in Biocatalysis and Agricultural Biotechnology. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Biocatalysis and Agricultural Biotechnology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
1
13
0
5
Order By: Relevance
“…The essential oil of this herb has been shown to have antioxidant activity. Other studies have reported antioxidant activities of water, methanol, and ethanolic cinnamon extracts [ 45 , 46 , 136 , 137 , 138 ]. This plant shows high anti-influenza virus activity [ 139 ].…”
Section: Antimicrobial Agentmentioning
confidence: 99%
“…The essential oil of this herb has been shown to have antioxidant activity. Other studies have reported antioxidant activities of water, methanol, and ethanolic cinnamon extracts [ 45 , 46 , 136 , 137 , 138 ]. This plant shows high anti-influenza virus activity [ 139 ].…”
Section: Antimicrobial Agentmentioning
confidence: 99%
“…In another study [ 34 ], purified PACs from M. philippinensis strongly inhibited the activity of α-glucosidase. The strong anti-glucosidase activity of C. burmannii water extract was attributed to polymers of PACs and other flavan-3-ols [ 14 ]. PACs were the main inhibitors of C. osmophloeum extract against carbohydrate-hydrolyzing enzymes [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cinnamon ( Cinnamomum spp.) is one of the most popular spices used worldwide [ 14 , 15 ]. In vitro and in vivo data show that cinnamon improves post-prandial hyperglycaemia, triglycerides, LDL cholesterol, total cholesterol, and prevents protein glycation [ 10 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kayu manis merupakan rempah pemberi cita rasa (flavor) di industri farmasi, kosmetik dan pangan serta sebagai obat tradisional maupun pengobatan modern (Sangal, 2011;Dhubiab, B. E., 2012) Kayu manis telah diketahui mengetahui senyawa bioaktif yang bermanfaat bagi kesehatan manusia. Kayu manis mengandung senyawa bioaktif seperti polifenol (termasuk flavonoid, tanin) dan senyawa minyak atsiri fenolik serta kumarin, polimer proantosianin tipe A dan heterodimeer terprotonasi gugus flavon-3ol, katekin, epikatekin, prosianidin B2, kuersetin, 3,4-dihidroksibenzaldehid, dan asam sinamat sebagai senyawa antioksidan utama (Ervina et al, 2016;Ervina et al, 2019;Kim et al, 2016;Muhammad et al, 2020;Sikand et al, 2015). Dalam studi tentang manfaat kayu manis untuk mencegah diabetes dan penyakit Alzheimer, Peterson et al, (2009) menemukan bahwa ekstrak air kulit kayu manis mengandung polifenol.…”
Section: Pendahuluanunclassified